2007
DOI: 10.1016/j.cell.2007.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Communication between Distant Sites in RNA Polymerase II through Ubiquitylation Factors and the Polymerase CTD

Abstract: Transcriptional arrest triggers ubiquitylation of RNA polymerase II (RNAPII). We mapped the yeast RNAPII ubiquitylation sites and found that they play an important role in elongation and the DNA-damage response. One site lies in a protein domain that is unordered in free RNAPII, but ordered in the elongating form, helping explain the preferential ubiquitylation of this form. The other site is >125 Angstroms away, yet mutation of either site affects ubiquitylation of the other, in vitro and in vivo. The basis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 28 publications
3
66
0
1
Order By: Relevance
“…Depending on the experimental conditions used, Rsp5 may predominantly add mono-ubiquitin or a polyubiquitin chain to RNAPII in vitro (6,12). Therefore, it is formally possible that in vivo, Rsp5 normally only adds mono-ubiquitin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the experimental conditions used, Rsp5 may predominantly add mono-ubiquitin or a polyubiquitin chain to RNAPII in vitro (6,12). Therefore, it is formally possible that in vivo, Rsp5 normally only adds mono-ubiquitin.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, degradation of RNAPII may be a ''last resort,'' used to clear active genes of persistently arrested RNAPII elongation complexes (6-9). Interestingly, the proteasome is nuclear and can be found on the coding region of genes by chromatin-immunoprecipitation (10), so RNAPII proteolysis may well occur on the DNA.We have reconstituted RNAPII ubiquitylation in vitro with highly purified, physiologically relevant yeast, or human, ubiquitylation factors, respectively (6,11,12). The yeast HECT E3 Rsp5 binds RNAPII via the flexible C-terminal repeat domain (CTD) of the Rpb1 subunit (13), but modifies the polymerase in the main body of the Rpb1 subunit (6,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rsp5 is the E3 ubiquitin ligase for DNA damage-induced ubiquitylation of RNAPII and binds the polymerase strongly, exclu-sively via the CTD (27,37,49). The physiological role, if any, of the Rsp5 stimulation of CTDK1 kinase activity remains to be determined.…”
Section: Dissociation Of Holo-rnapii Does Not Require Holo-tfiihmentioning
confidence: 99%
“…The E3 ligase recognizes the substrate protein and provides specificity to the reaction, although a recent study showed that an E2 may also function in target recognition (58). E3 ubiquitin ligases can be divided into two major classes that contain either a HECT (homologous to E6-AP carboxyl terminus) domain or a RING (really interesting new gene) finger domain and differ in the mechanism by which ubiquitin is transferred to the target protein.…”
Section: The Ubiquitin Machinerymentioning
confidence: 99%